Improving the synchronisation of supply chains: an automotive case study. (14th February 2005) - Lyons, Andrew; Coronado, Adrian; Kehoe, Dennis; Coleman, Julian
The authors report on an attempt to examine the theory, practical feasibility and benefits of making vehicle build information accessible to second and third-tier component suppliers. A description is provided of a case study used to demonstrate the impact on supply chain performance of sharing vehicle build information with the upstream suppliers of a high-volume vehicle manufacturer. A range of performance measures aggregated in the form of a "supply chain scorecard" demonstrated that suppliers are able to synchronise manufacturing more closely with the vehicle manufacturer and make capacity utilisation, lead time and inventory improvements with access to vehicle production schedules.